Transcriptome analysis of the biofilm formation mechanism of Vibrio parahaemolyticus under the sub-inhibitory concentrations of copper and carbenicillin - Xie, Jiaying; Zhang, Hongmin; Li, Yinhui; Li, Hao; Pan, Yingjie; Zhao, Yong; Xie, Qingchao (Frontiers in Microbiology, 2023)
Biofilm formation of Vibrio parahaemolyticus enhanced its tolerance to the environment, but caused many serious problems to food safety and human health. In this paper, the effects of copper and carbenicillin (CARB) stress on the formation of the biofilms of V. parahaemolyticus organisms were studied, and RNA sequencing technology was used to compare the differences in transcriptome profiles of the biofilm-related genes of V. parahaemolyticus organisms under different sub-inhibitory stresses. The results proved that V. parahaemolyticus had a large growth difference under the two stresses, copper and CARB at 1/2 minimal inhibitory concentration (MIC), and it could form a stable biofilm under both stress conditions. The amount of biofilm formed under CARB stress was significantly higher than that of copper stress (P<0.05). Based on the analysis of transcriptome sequencing results 323, 1550 and 1296 significantly differential expressed genes were identified in the three treatment groups namely 1/2 MIC CARB, Cu2+ and Cu2++CARB. Through COG annotation, KEGG metabolic pathway analysis and gene expression analysis related to biofilm formation, the functional pathways of transcriptome changes affecting V. parahaemolyticus were different in the three treatment groups, and the CARB treatment group was significantly different from the other two groups. These differences indicated that the ABC transport system, two-component system and quorum sensing were all involved in the biofilm formation of the V. parahaemolytic by regulating flagellar motility, extracellular polysaccharides and extracellular polymer synthesis. Exploring the effects of different stress conditions on the transcriptome of V. parahaemolyticus could provide a basis for future research on the complex network system that regulates the formation of bacterial biofilms.